The mediating role of psychological resilience in the relationship between epidemic anxiety and academic motivation of physical education teacher candidates - Mustafa Enes Işıkgöz; Turan Sezan; Abdullah Yüksel (Physical Education of Students, 2023)
Background and Study Aim. In addition to their physiological effects, epidemics negatively affect the motivation of individuals by causing varying levels of psychosocial problems such as stress, fear, anxiety and depression. At this point, psychological resilience is considered as an important variable in reducing and preventing the psychological effects of epidemic anxiety. The main purpose of this study is to examine the mediating role of psychological resilience in the relationship between epidemic anxiety of physical education teacher candidates and their academic motivation.